Corporate Governance Country Assessment : Republic of Korea - World Bank (Washington, DC, 2013)
Since 1998, Korea has taken important steps to address the weaknesses that contributed to the economic crisis of 1997. The corporate governance framework has been strengthened significantly. The reform agenda, however, remains unfinished and the equity markets relative to other OECD countries remain underdeveloped. There has been good progress in upgrading accounting and auditing standards and practices, as well as strengthening underlying institutions responsible for setting standards and ensuring compliance. The Financial Supervisory Commission/Financial Supervisory Services have been established, and the role of the Korean Institute of Certified Public Accountants has been strengthened. Efforts should continue to further improve accounting standards and improve accounting and auditing practices, and include measures to clarify and strengthen the role and function of audit committees consistent with international best practices; replace statutory auditors with audit committees for smaller companies over time; and upgrade the skills and knowledge of audit committee members. While holding companies are allowed, only several of them have been established. In order to improve transparency and disclosures of chaebol-affiliated operations, consider several measures including measures that may change the incentives for large chaebol to establish holding companies (e.g. lower taxes). While significant improvements have been made to increase minority shareholder rights (e.g., by lowering or eliminating threshold ownership requirements) and the ease with which shareholders exercise those rights, further improvements are required, including measures to allow minority shareholders a greater voice in the selection of directors and steps to improve the process for nominating independent directors. While derivative actions are allowed, these are costly and therefore have been limited so far to only a few. The redress available to shareholders if their rights are violated remains limited, and there is no cost-effective way for them to seek redress. The draft law submitted to the National Assembly allowing class action lawsuits should be enacted as soon as possible. Securities laws have been amended to require listed companies to have outside directors. However, the concept of independent (outside) directors is new and still not well rooted in Korea. Additional efforts could include measures to expand the fiduciary duty of directors to shareholders and make it explicit under the law, and to limit liability of independent directors in cases in which they have acted in good faith.